RIPK4 suppresses the TGF‐β1 signaling pathway in HaCaT cells. (19th December 2019) - Dinçer, Tuba; Boz Er, Asiye Büşra; Er, İdris; Toraman, Bayram; Yildiz, Gokhan; Kalay, Ersan
Abstract: Receptor‐interacting serine/threonine kinase 4 (RIPK4) and transforming growth factor‐β 1 (TGF‐β1) play critical roles in the development and maintenance of the epidermis. A negative correlation between the expression patterns of RIPK4 and TGF‐β signaling during epidermal homeostasis‐related events and suppression of RIPK4 expression by TGF‐β1 in keratinocyte cell lines suggest the presence of a negative regulatory loop between the two factors. So far, RIPK4 has been shown to regulate nuclear factor‐κB (NF‐κB), protein kinase C (PKC), wingless‐type MMTV integration site family (Wnt), and (mitogen‐activated protein kinase) MAPK signaling pathways. In this study, we examined the effect of RIPK4 on the canonical Smad‐mediated TGF‐β1 signaling pathway by using the immortalized human keratinocyte HaCaT cell line. According to our results, RIPK4 inhibits intracellular Smad‐mediated TGF‐β1 signaling events through suppression of TGF‐β1‐induced Smad2/3 phosphorylation, which is reflected in the upcoming intracellular events including Smad2/3‐Smad4 interaction, nuclear localization, and TGF‐β1‐induced gene expression. Moreover, the kinase activity of RIPK4 is required for this process. The in vitro wound‐scratch assay demonstrated that RIPK4 suppressed TGF‐β1‐mediated wound healing through blocking TGF‐β1‐induced cell migration. In conclusion, our results showed the antagonistic effect of RIPK4 on TGF‐β1 signaling in keratinocytes for the first time and have the potential to contribute to the understanding and treatment of skin diseases associated with aberrant TGF‐β1 signaling.